2004
DOI: 10.1148/radiol.2331031208
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography and Colonoscopy: Assessment of Patient Preference in a 5-week Follow-up Study

Abstract: Patients preferred CT colonography to colonoscopy; however, this preference decreased in time, while outcome considerations gradually replaced temporary experiences of inconvenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 35 publications
(41 reference statements)
4
83
0
1
Order By: Relevance
“…However, at 3 months, they were more satisfied with how results were received (median score of 4 [IQR,[3][4], P , .0005) and less likely to require follow-up colonic investigations (17 of 230 vs 37 of 107, P , .0005). No differences were observed between the tests regarding 3-month psychologic consequences of the diagnostic episode, except for a trend toward a difference (P = .050) in negative affect (unpleasant emotions such as distress), with patients undergoing CT colonography reporting less intense negative affect.…”
Section: Resultsmentioning
confidence: 99%
“…However, at 3 months, they were more satisfied with how results were received (median score of 4 [IQR,[3][4], P , .0005) and less likely to require follow-up colonic investigations (17 of 230 vs 37 of 107, P , .0005). No differences were observed between the tests regarding 3-month psychologic consequences of the diagnostic episode, except for a trend toward a difference (P = .050) in negative affect (unpleasant emotions such as distress), with patients undergoing CT colonography reporting less intense negative affect.…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire was designed using questions previously used in evaluation of bowel preparation [20][21][22], using a Likert scale with seven points employed for each question [23]. A variety of potential side-effects from the bowel preparation were interrogated as follows: general disruption to daily life, overall discomfort, abdominal pain, diarrhoea, anal irritation, thirst, hunger, nausea and vomiting.…”
Section: Patient Experiencementioning
confidence: 99%
“…However, there have been reports about a possible correlation between nephrogenic fibrosing dermopathy (NFD) and the intravenous administration of gadolinium compounds (20). As far as patient acceptance is concerned, several trials revealed a higher acceptance rate for virtual colonography compared to optical endoscopy (21)(22)(23). The need to undergo bowel cleansing yet is rated as the most unpleasant part of the virtual colonography exam (21-25) and patient discomfort scores can be significantly improved with tagging preparations previously shown for CT colonoscopy (CTC) (26).…”
Section: Discussionmentioning
confidence: 99%